Validity of medico-administrative data related to amyotrophic lateral sclerosis in France: A population-based study. Issue 1 (2nd January 2017) - Vasta, Rosario; Boumédiene, Farid; Couratier, Philippe; Nicol, Marie; Nicoletti, Alessandra; Preux, Pierre-Marie; Marin, Benoit; ,
Abstract: The accuracy of French medico-administrative data concerning amyotrophic lateral sclerosis (ALS) is to date unknown. We aimed to assess the validity of hospital discharge data (HDD) and health insurance data (HID) related to ALS. A retrospective population-based study was performed. The French register of ALS in Limousin (FRALim) was used as gold standard (2000–2013 period). All patients discharged from the regional hospitals with a 'G12.2' code in their HDD (according to the International Classification of Disease-10th version) or having a G12 HID code were considered. In the study period, the register included a total of 322 incident ALS patients. Among 451 subjects identified through HDD, 290 were true incident ALS cases, corresponding to 90.1% (95% CI 86.3–93.1) sensitivity and 64.3% (95% CI 59.7–68.7) positive predictive value (PPV). A total of 184 subjects were identified through HID, 142 of which were true ALS cases. This corresponded to 44.1% (95% CI 38.6–49.7) sensitivity and 75.5% (95% CI 68.7–81.5) PPV. The combination of both HDD and HID led to 93.8% (95% CI 90.6–96.2) sensitivity and 60.8% (95% CI 56.3–65.1) PPV. This study shows that French HDD and HID, even if combined, are not per se suitable for accurate and exhaustive direct identification of ALS cases.